Exploring the causes of obstructive jaundice: a single-centre retrospective analysis - Murshid, Mohsin Yahya; Al-Alhazmi, Abdulellah Talal; Ansari, Farrukh Alim (International Surgery Journal, 2024)
Background: Obstructive jaundice is a condition caused by bile flow blockage and has various benign and malignant etiologies. Accurate and timely diagnosis is essential for effective treatment, particularly in cases of possible malignancy. Advances in diagnostic methods have improved our understanding and management of diseases. This study aimed to investigate the causes and clinical presentation of obstructive jaundice in Saudi Arabian population. Methods: This study included 193 patients diagnosed with obstructive jaundice admitted to the surgical wards from January 2019 to December 2022. Methods involved comprehensive clinical evaluations, medical history reviews, physical examinations, laboratory tests, and diagnostic imaging to identify the underlying disease. Data were collected systematically and statistically analyzed. Results: The study included 193 patients with a male-to-female ratio of 1:1.4, and an average age of 54.10 years. Malignant causes, primarily carcinoma of the pancreatic head, accounted for 59.4% of cases, while benign causes, notably choledocholithiasis, accounted for 41.6%. Symptoms included jaundice, abdominal pain, and loss of appetite, with treatment varying according to the identified cause. Conclusions: The study highlights that obstructive jaundice is more commonly found in females and tends to be caused by benign conditions in younger people, while malignant causes are more prevalent in older individuals. The most common malignant cause is carcinoma of the pancreatic head, and leading benign cause is choledocholithiasis. For diagnosing obstructive jaundice, key imaging techniques include magnetic resonance cholangiopancreatography (MRCP), endoscopic retrograde cholangiopancreatography (ERCP), and computed tomography (CT).